GPR87 promotes tumor cell invasion and mediates the immunogenomic landscape of lung adenocarcinoma - Rui Bai; Jianguo Zhang; Fajian He; Yangyi Li; Panpan Dai; Zhengrong Huang; Linzhi Han; Zhihao Wang; Yan Gong; Conghua Xie (Communications Biology, 2022)
GPR87 is reported as a central player in lung adenocarcinoma and in resistance to immunotherapy, by promoting tumor cell invasion and mediating the immunogenomic landscape.